Acute Neonatal Parotitis with Late-Onset Septic Shock due to Streptococcus agalactiae - M. Boulyana (Case Reports in Pediatrics)
Acute neonatal parotitis (ANP) is a very rare disease. Most cases are managed conservatively; early antibiotics and adequate hydration may reduce the need for surgery. The most common cause of ANP is Staphylococcus aureus. We report a rare case of acute neonatal parotitis with late-onset septic shock due to Streptococcus agalactiae. The diagnosis was confirmed with ultrasound and isolation of Streptococcus agalactiae from blood culture. The patient was treated successfully with 10 days of intravenous antibiotics and supportive measures. Despite being rare, streptococcal ANP should be considered in the etiological diagnosis of neonatal sepsis. Early diagnosis and appropriate antibiotic might prevent serious complications.